2020
DOI: 10.1108/ijchm-05-2019-0438
|View full text |Cite
|
Sign up to set email alerts
|

Does servant leadership better explain work engagement, career satisfaction and adaptive performance than authentic leadership?

Abstract: Purpose The purpose of this paper is to propose a research model in which work engagement (WENG) mediates the effects of servant leadership (SL) and authentic leadership (AL) simultaneously on career satisfaction and adaptive performance. It also aims to test whether SL better explains WENG and the aforesaid outcomes than AL. Design/methodology/approach Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
200
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(226 citation statements)
references
References 57 publications
15
200
0
11
Order By: Relevance
“…This is to assure that the questionnaire when translated to Turkish language did not lose the initial intent of the questions (Tarkang, Alola, Nange, & Ozturen, 2020). A pilot study was conducted with a sample of five questionnaires; this is to ensure that the questions are readable and comprehensive (Kaya & Karatepe, 2020). However, there was no need for modifications of the questionnaire after the pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…This is to assure that the questionnaire when translated to Turkish language did not lose the initial intent of the questions (Tarkang, Alola, Nange, & Ozturen, 2020). A pilot study was conducted with a sample of five questionnaires; this is to ensure that the questions are readable and comprehensive (Kaya & Karatepe, 2020). However, there was no need for modifications of the questionnaire after the pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical evidences also have supported job engagement as the precursor of organizational performance (Bhatti et al, 2018;Huang et al, 2018). Engaged employees work with their physical energy, emotional energy, and affective energy with dedication (Albrecht et al, 2018;Kaya & Karatepe, 2020;Adil & Khan, 2020;Truss et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Job engagement has become a thought-provoking topic among the academic researchers in recent years Rabiul & Yean, 2021;Adil & Khan, 2020). Job engagement is consistently found to be the key antecedent of organizational performance (Albrecht et al, 2018;Attridge, 2009;Kaya & Karatepe, 2020;Adil & Khan, 2020). Empirical evidences also have supported job engagement as the precursor of organizational performance (Bhatti et al, 2018;Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term satisfaction and retention of employees is an important domain of SHRM. Research has generally showed a positive linkage between employee work engagement (EWE), work satisfaction, and stay intention [5,6]. As a result, an important SHRM issue is to increase EWE, reduce turnover rates, and achieve sustainable long-term employee retention.…”
Section: Introductionmentioning
confidence: 99%